Teacher Preparation in Zambia's Expanded Core Curriculum: Challenges and Opportunities - Magdalene Simalalo; Velisiwe G. Gasa; Kenneth K. Muzata (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2022)
Well-prepared teachers are a determinant in the successful implementation of expanded core curriculum. Teachers can give learners skills according to the way they are prepared. Learners with visual impairments in special schools and students at tertiary level manifest deficits in critical skills required in academic success and transition in general. The nature of education of their teachers and challenges encountered during teacher preparation were not well established. The present study explored challenges faced in the preparation of teachers of learners with visual impairments in expanded core curriculum. Purposive sampling was used to select twenty-two teachers, two special education curriculum specialists and three Teacher educators. Open-ended questionnaires were used to collect data from teachers of learners with visual impairments and semi structured interviews were conducted with teacher educators and curriculum specialists. The findings indicated that teacher education/preparation in ECC was insufficient, and the institutions concentrated on braille literacy; and orientation and mobility. The remaining skills in ECC were ignored. Preparation incorporated few practical sessions and was highly theoretical. The major challenges among others were time constraints; insufficient resources in education; enrolments of student teachers; discrepancy between education and implementation; methodological issues. The opportunities were available to improve education were: employ more staff; embark on specialised education; advocacy and collaboration: offering continuous professional development for teachers. The study highlights the nature of preparation of teachers of learners with visual impairment. The teacher education institutions need to realign the curriculum through collaborative approach with other stakeholders so that teachers can effectively deliver skills to the learners.